Effects of islet neogenesis associated protein depend on vascular endothelial growth factor gene expression modulated by hypoxia-inducible factor 1-alpha - Román, Carolina Lisi (2019)
Background Pharmacology has provided efficient tools to improve insulin effect/secretion but the decrease in β-cell mass remains elusive. INGAP-PP could provide a therapeutic alternative to meet that challenge. Aim To further understand the mechanism that links INGAP-PP effects upon β-cell mass and function with islet angiogenesis. Methodology Normal male Wistar rats were divided into 2 groups and injected with a single dose of 100 mg/Kg suramin or saline. Both groups were divided into 2 subgroups that received daily doses of 2 mg/kg INGAP-PP or saline for ten days. Plasma glucose, triacylglycerol, TBARS, and insulin levels were measured. Pancreas immunomorphometric analyses were also performed. Pancreatic islets were isolated to measure glucose-stimulated insulin secretion (GSIS). Specific islet mRNA levels were studied by qRT-PCR. Statistical analysis was done using ANOVA. Results No differences were recorded in body weight, food intake, or any other plasma parameter measured in all groups. Islets from INGAP-PP-treated rats significantly increased GSIS, β-cell mass, and mRNA levels of Bcl-2, Ngn-3, VEGF-A, VEGF-R2, CD31, Ang1 and Ang2, Laminin β-1, and Integrin β-1, and decreased mRNA levels of Caspase-8, Bad, and Bax. Islets from suramin-treated rats showed significant opposite effects, but INGAPP-PP administration rescued most of the suramin effects in animals treated with both compounds. Conclusion Our results reinforce the concept that INGAP-PP enhances insulin secretion and β-cell mass, acting through PI3K/Akt/mTOR pathways and simultaneously activating angiogenesis through HIF-1α-mediated VEGF-A secretion. Therefore, INGAP-PP might be a suitable antidiabetic agent able to overcome two major alterations present in T2D.